SIKAP BUDAYA MASYARAKAT NELAYAN TERHADAP PENDIDIKAN ANAK PADA DESA GOLO MENI KECAMATAN KOTA KOMBA UTARA KABUPATEN MANGGARAI TIMUR - Fridolina Purnawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The objectives of this study were to discover the fisherman's attitude toward children's education, as well as the attitude constraints that fishing communities experience when sending their children to the school. The study is descriptive qualitative, with data collection through observation, interviews, and documentation. The headman and fishermen become the subject of research. The data's validity was determined by data collection, data reduction, data presentation, and drawing conclusions. According to the findings of this study, fishing communities are tough and open-minded, hard workers but apathetic. It is caused by the fact that they are frequently disappointed or fooled by loved ones. Challenges that fishing communities confront in sending their children to school must be examined, as well as children's attitudes toward education, familial relationships, and the effect of the social environment. Another finding is that some fishermen think that they prioritize work as fishermen rather than continuing their children's education.